Implications of Constructivism Theory for the Development of Islamic Religious Education Curriculum - Hikma Apriyani; Agus Pahrudin; Agus Jatmiko; Koderi (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
This study explores the implications of constructivist theory on the development of the Islamic Religious Education (PAI) curriculum. The research highlights how the application of constructivist approaches in PAI can enhance student engagement, understanding of religious concepts, and critical thinking skills. Data collected through surveys and interviews indicate that 85% of students feel more interested and active in learning when constructivist methods are applied. Furthermore, the findings reveal a significant increase in students' academic performance, with mastery rates rising from 66% to 91% after implementing constructivist strategies. The role of teachers as facilitators is emphasized, as they guide students in constructing their knowledge. However, challenges such as limited teacher understanding of constructivism and inadequate educational facilities persist. To address these issues, it is recommended that schools provide professional development for teachers and foster a collaborative school culture that supports active learning. The study concludes that integrating constructivist principles into the PAI curriculum can lead to a more relevant and effective educational experience for students, ultimately shaping a generation with strong character and deep religious understanding.